The drop-jump video screening test: retention of improvement in neuromuscular control in female volleyball players - Barber-Westin, S. D.; Smith, S. T.; Campbell, T.; Noyes, F. R. (The Journal of Strength and Conditioning Research, 2010)
A valgus lower limb alignment is commonly documented during noncontact anterior cruciate ligament injuries. We previously developed a videographic drop-jump test to measure overall lower limb alignment in the coronal plane as a screening tool to detect such an abnormal (valgus) position on landing. A neuromuscular retraining program developed for female athletes was shown to be effective in improving lower limb alignment on this test immediately after completion of training. What remained unknown was whether these improvements would be retained for longer periods of time. Therefore, this study was undertaken to determine if these improvements in overall lower limb alignment would be retained up to 1 year after the training. Sixteen competitive, experienced female high-school volleyball players underwent the video drop-jump test and then completed the neuromuscular retraining program. The program consisted of a dynamic warm-up, jump training, speed and agility drills, strength training, and static stretching and was performed 3 times a week for 6 weeks. The athletes repeated the drop-jump test immediately upon completion of training and then 3- and 12-months later. Significant improvements were found in the mean normalized knee separation distance between the pre and posttrained values for all test sessions (p < 0.01). Immediately after training, 11 athletes (69%) displayed significant improvements in the mean normalized knee separation distance that were retained 12 months later. Five athletes failed to improve. The video drop-jump test, although not a risk indicator for a knee ligament injury, provides a cost-effective general assessment of lower limb position and depicts athletes who have poor control on landing and acceleration into a vertical jump.